MELATIHKAN KETERAMPILAN PROSES SAINS MAHASISWA BIOLOGI MELALUI PENGEMBANGAN PERANGKAT PEMBELAJARAN GUIDED INQUIRY PADA POKOK BAHASAN KLASIFIKASI TUMBUHAN - Taufik Samsuri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: Skills Process Sciences (KPS) is the ability to use the mind, reason and deeds based on scientific process. KPS needs to be developed because with the skills of the process one will be able to learn independently, develop themselves, and learn throughout life. Scientific process skills are a necessary skill in doing research and solving problems. This problem solving ability is one of Life Skills (Life Skills) that students need to have in order to continue their life. Based on the above description, the objective of the research is to produce a guided inquiry instructional device to trace the skills of biology student science process on the subject of Plant Classification. This type of research is an experimental research with research design using one group pre-test post-test design. The results show that learning tools developed (syllabus, SAP, and MFI) are well categorized, while students' science process skills, high N-gain values on communicating skills, and moderate categories of inferencing, analyzing, and designing experimental designs.